USE OF WOUND PROTECTOR FOR PREVENTION OF SURGICAL SITE INFECTION IN LAPAROSCOPIC CHOLECYSTECTOMY (World Science, 2020)
The work is based on the experience of 759 cholecystectomies performed in 2015-2018. Patients with a 3-4 grades of microbial contamination of wounds were divided into two groups: the first, with removal of the gallbladder traditionally with specimen retrieval container and the second, where proposed method of combined use of container and wound protector was used − 19 patients.Surgical site infection in laparoscopic cholecystectomy was detected in 5.40% (41 patients out of 759). During surgical interventions related to the second grade of microbial contamination (clean-contaminated), the frequency of SSI was 2.50%, to the third grade (contaminated) − 11.76%, and to the fourth grade (dirty) − 34.92%. Using the proposed method for the simultaneous use of the retrieval container and the double-ring wound protector in the second and third grades of wounds in LC allowed to reduce the frequency of SSI from 37.70% to 5.26%.